Calcium-induced Cardiac Mitochondrial Dysfunction Is Predominantly Mediated by Cyclosporine A-dependent Mitochondrial Permeability Transition Pore - Chontida Yarana (2018)
Background and Aims: Cardiac mitochondrial Ca2+overload plays a critical role in mechanical and electrical dysfunction leading to cardiac cell death and fatal arrhythmia. Because Ca2+overload is related to mitochondrial permeability transition, reactive oxygen species (ROS) production and membrane potential (ΔΨm) dissipation, we probed the mechanistic association between Ca2+overload, oxidative stress, mitochondrial permeability transition pore (mPTP) and mitochondrial calcium uniporter (MCU) in isolated cardiac mitochondria. Methods: Various concentrations of Ca2+(5-200 μM) were used to induce mitochondrial dysfunction. Cyclosporin A (CsA, an mPTP blocker) and Ru360 (an MCU blocker) were used to test its protective effects on Ca2+-induced mitochondrial dysfunction. Results: High concentrations of Ca2+(≥100 μM) caused overt mitochondrial swelling and ΔΨm collapse. However, only slight increases in ROS production were detected. Blocking the MCU by Ru360 is less effective in protecting mitochondrial dysfunction. Conclusions: A dominant cause of Ca2+-induced cardiac mitochondrial dysfunction was mediated through the mPTP rather than MCU. Therefore, CsA could be more effective than Ru360 in preventing Ca2+-induced cardiac mitochondrial dysfunction. © 2012 IMSS.